Answer:
2(x-2y)/(4x-y) = dy/dx
Step-by-step explanation:
2x^2+y^2=8xy
Take the derivative of each term, remembering that we take the 8xy as derivative by parts)
2 * 2x dx + *2y dy = 8 ( x dy + dx *y)
4x dx +2y dy = 8x dy + 8y dx
Subtract 2y dy from each side
4x dx +2y dy -4y dy = 8x dy - 2y dy + 8y dx
4x dx = 8x dy - 2y dy + 8y dx
Subtract 8y dx from each side
4x dx -8y dx = 8x dy - 2y dy + 8y dx-8y dx
4x dx -8y dx = 8x dy - 2y dy
(4x-8y) dx = (8x-2y) dy
Factor out a 4 from the left side and a 2 from the right side
4(x-2y) dx = 2( 4x-y) dy
Cancel a 2
2(x-2y) dx = ( 4x-y) dy
Divide each side by (4x-y)
2(x-2y)/(4x-y) dx = ( 4x-y)/(4x-y) dy
2(x-2y)/(4x-y) dx = dy
Divide by dx
2(x-2y)/(4x-y) dx/dx = dy/dx
2(x-2y)/(4x-y) = dy/dx